MODEL SUPERVISI MADRASAH: SEBUAH ANALISIS BIBLIOMETRIK - Abd. Rahman Ambo’ Dalle; Habibur Rahman; Fadhil Ismail; Indah Aminatuz Zuhriyah; Baharuddin; Sutrisno (EBTIDA': Jurnal Pendidikan Dasar Islam, 2026)
This study aims to map research trends and identify madrasah supervision models through bibliometric analysis. The method employed a systematic literature review based on the PRISMA protocol and bibliometric analysis using VOSviewer software on 31 English-language articles indexed in Scopus. The results show that Indonesia is the most productive country, contributing 26 publications and 104 citations, while Malaysia has the strongest international collaboration network (TLS=368). Publication trends peaked in 2025 with 14 articles. Keywords such as educational quality, Islamic leadership, employee performance, job satisfaction, financial management, and public administration & management each have a TLS of 8, indicating strong connections to the topic of madrasah supervision. These findings lead to the formulation of an integrative madrasah supervision model that combines improving educational quality, Islamic leadership, performance management, job satisfaction, and financial and administrative management within a systemic framework.